2021
DOI: 10.3389/fnut.2021.628628
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Low Handgrip Strength and 90-Day Mortality Among Older Chinese Inpatients: A National Multicenter Prospective Cohort Study

Abstract: Background: The knowledge of the association between low handgrip strength and mortality among older Chinese inpatients is limited. Given China's aging society, a great number of older adults require hospital admission.Objective: To explore the association between low handgrip strength and 90-day mortality, providing evidence for clinicians to predict the risk of mortality and improve clinical outcomes for older inpatients.Materials and Methods: We conducted a national multicenter cohort study with a baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Participants will stand with feet shoulder-width apart, body upright, holding the electronic handgrip meter down, then according to researcher’s instruction, they will exert maximum force for 2 seconds. Adequate rest will be given between the two measurements 32 . Overall functional ability will be measured by the Timed Up and Go test (TUGT) 33 , which requires an armless chair and a stopwatch.…”
Section: Discussionmentioning
confidence: 99%
“…Participants will stand with feet shoulder-width apart, body upright, holding the electronic handgrip meter down, then according to researcher’s instruction, they will exert maximum force for 2 seconds. Adequate rest will be given between the two measurements 32 . Overall functional ability will be measured by the Timed Up and Go test (TUGT) 33 , which requires an armless chair and a stopwatch.…”
Section: Discussionmentioning
confidence: 99%
“…Our data also demonstrated that the irisin concentration was lower in the elder subjects ( 83 ). It has been noticed that the age could influence the handgrip strength, although the factors contributing for lower handgrip strength variated in different studies with different designs ( 84 86 ). The influence of aging might also be altered by increasing the sample size or altering the enrollment criteria accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers propose that the prevalence of sarcopenia is related to CVD risks in elderly adults. Numerous evidence have reported that patients with low handgrip strength are at risk of CVD mortality (22) . In a cross-sectional study, physical disability is suggested an important risk factor for CVD mortality in elderly adults (23) .…”
Section: Discussionmentioning
confidence: 99%